Dinamika Aspek Kesehatan dan Ekonomi dalam Kebijakan Pengendalian Minuman Berkarbonasi di Indonesia - Zeni Zaenal Mutaqin (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
Consumption of carbonated beverages in Indonesia always increases every year. Increased non-communicable diseases associated with consumption of carbonated beverages such as obesity and type 2 diabetes have increased. The World Health Organization (WHO) encourages all governments in the world to take preventive measures through fiscal and non-fiscal policies. Currently in Indonesia there is no policy to control the consumption of carbonated beverages. Based on previous research, it is stated that economic factor is very big influence to the formation of health policy in Indonesia. This study aims to describe the dynamics of health and economic factors in the formation of carbonated beverage control policy through excise in Indonesia. The research method is a descriptive study with qualitative analysis method by conducting in-depth interviews, document tracking, and litelatur study. The results concluded that economic factors are preferred from health factors. Whereas based on estimates, economic losses are much greater than the tax contributions provided by the beverage industry. It is recommended that the government make health factor a top priority in the formation of health policy. To prevent the high health problems caused by the consumption of carbonated beverages, the government should make carbonated beverages as taxable goods. Keywords: Health policy, health economy, control of carbonated drinks